PENGEMBANGAN PHYSICS MAGAZINE BERBASIS ARGUMENT-DRIVEN INQUIRY UNTUK MENINGKATKAN KETERAMPILAN ARGUMENTASI SISWA - Sari, Rika Sumita Wimanda; Ahmad, Nur; Rusdianto (Information Technology Education Department, 2025)
could encourage students to express their opinions, so media was needed that could improve students' argumentation skills. The purpose of this research was to produce teaching materials in the form of Argument-Driven Inquiry-based Physics Magazine to improve students' argumentation skills. This research method was research and development (R&D) with the ADDIE development model. The research involved 28 students of class VIII-B at MTs Negeri 2 Jember as the sample. The results showed the validity percentage of Physics Magazine was 97% (very valid), practicality was 88% (very practical), and N-gain was 0.60 (medium), and student responses reached 88% (very good). Aspects of claim, ground/data, and warrant showed high improvement, while backing, qualifier, and rebuttal showed moderate improvement. Physics Magazine based on Argument-Driven Inquiry met the criteria of validity, practicality, and effectiveness because it was arranged systematically according to the stages of Argument-Driven Inquiry and included all indicators of argumentation skills. Physics Magazine was feasible to be implemented in learning and could improve students' argumentation skills with moderate influence. This research provided alternative teaching materials that were innovative, interesting, and could be used by teachers in learning, especially to improve students' argumentation skills. Future research was expected to develop teaching materials with a focus on improving argumentation skills on backing, qualifier, and rebuttal indicators.